Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1172/jci115401
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of prostaglandin F2 alpha in Zellweger syndrome. Peroxisomal beta-oxidation is a major importance for in vivo degradation of prostaglandins in humans.

Abstract: We have recently shown in vitro that the peroxisomal fraction of a rat liver homogenate has the highest capacity to (-oxidize prostaglandins. In order to evaluate the relative importance of peroxisomes for this conversion also in vivo, we administered [Hjprostaglandin F2. to an infant suffering from Zellweger syndrome, a congenital disorder characterized by the absence of intact peroxisomes. As a control, labeled compound was administered to two healthy volunteers. Urine was collected, fractionated on a SEP-PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 31 publications
(18 reference statements)
3
23
0
Order By: Relevance
“…In contrast to healthy children, none of these p-oxidized major urinary metabolites could be detected by GC-MSMS in urine of children with ZS. The complete absence of PGF-MUM and 2,3-dinor-TxB, in the urine from children with ZS is in line with other reports (18,19). Importantly, we found a new metabolite of the E PG in urine.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast to healthy children, none of these p-oxidized major urinary metabolites could be detected by GC-MSMS in urine of children with ZS. The complete absence of PGF-MUM and 2,3-dinor-TxB, in the urine from children with ZS is in line with other reports (18,19). Importantly, we found a new metabolite of the E PG in urine.…”
Section: Discussionsupporting
confidence: 92%
“…All these signals are increased by 54 D [CH=CH-(CH,),] with respect to the signals of the PFB-MO-TMS derivative of PGF-MUM. On the basis of the present data, we suggest that this metabolite is identical with 9,ll-dihydroxy-15-0x0-prost-5-ene-1,20-dioic acid, which is identical with that described by Diczfalusy et al (18).…”
Section: Zssupporting
confidence: 89%
See 2 more Smart Citations
“…Peroxisomal ␤-oxidation of very long-and longchain CoA esters results in chain shortening of fatty acids, which may then be transported to the mitochondria as carnitine esters for further oxidation. ␤-Oxidation of other types of lipids such as prostanoids leads to chain shortening in the peroxisome for excretion as free carboxylic acids in the urine (3). Almost 30 years ago a group of compounds was identified that were shown to cause peroxisome proliferation in rodents; hence they were named peroxisome proliferators.…”
mentioning
confidence: 99%